Global waveshape parameter Rd in signaling focal prominence: Perceptual salience in the absence of f0 variation - Yanushevskaya, Irena; Murphy, Andy; Gobl, Christer; Ní Chasaide, Ailbhe (Frontiers in Communication, 2022)
This paper explores perceptual salience of voice source parameter manipulation in signalling prominence in the absence of f0 variation. Synthetic stimuli were generated based on an inverse filtered all-voiced utterance ‘We were away a year ago’. A global waveshape parameter Rd was manipulated in the stimuli to enhance prominence in the two potentially accentable syllables WAY and YEAR and to provide voice source deaccentuation post-focally. The manipulations were intended to mimic an increase in phonatory tension in the prominent syllable while decreasing it in the post-focal material. f0 was kept constant. Two listening tests were conducted in which participants rated perceived prominence of the potentially accentable syllables in the manipulated utterances on a continuous visual analogue scale. The results suggest that perceived focal prominence can be achieved by source variation in the absence of f0 modulations, although the results were not identical in the two tests. The extent of the enhancement of prominence by source manipulations in our data depended on the location of focal syllable in the intonational phrase and on the length of postfocal material (effect was stronger for WAY than for YEAR).